The diagnostic value of contrast-enhanced transcranial Doppler and contrast-enhanced transthoracic echocardiography for right to left shunt in patent foramen ovale: a systematic review and meta-analysis - Zhang, Dian; Jiang, Li; Chen, Yue-Nan; Pan, Mei-Fang (Frontiers in Neurology, 2024)
Purpose: To evaluate and compare the diagnostic value of contrast-enhanced transcranial Doppler (c-TCD) and contrast-enhanced transthoracic echocardiography (c-TTE) for right to left shunt (RLS) in patent foramen ovale (PFO) by meta-analysis. Methods: The literature included in the Cochrane Library, PubMed, and Embase were searched by using "contrast-enhanced transcranial Doppler (c-TCD), contrast-enhanced transthoracic echocardiography (c-TTE), patent foramen ovale (PFO), and right to left shunt (RLS)" as the keywords from inception through April 30, 2024. The diagnostic accuracy research quality assessment tool (QUADAS-2) was used to evaluate the quality of the included literature. The combined sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), and Diagnostic odds ratio (DOR) were pooled, and a comprehensive ROC curve analysis was performed. Statistical software StataSE 12.0 and Meta-Disc 1.4 were used for data analysis. Results: A total of 8536 articles were retrieved, and 9 articles that met all inclusion criteria were included in this meta-analysis. The meta-analysis results show that the combined sensitivity, specificity, PLR, NLR, DOR, and area under the SROC curve of c-TCD for the diagnose of PFO-RLS were 0.